Teachers' Perspectives on Academic Ability Test Implementation concerning National Education Regulations - Nurlista Iryanti; Novita Sari (Universitas Indo Global Mandiri, 2025)
The Academic Ability Test (Tes Kemampuan Akademik/TKA), mandated by Regulation of the Ministry of Education and Culture Number 045/H/AN/2025, aims to standardize academic assessment in Indonesian senior high and vocational schools. This study examines teachers’ perspectives on TKA implementation, focusing on teachers’ understanding of the regulation, students’ readiness, and students’ attitudes toward the test. Using a descriptive qualitative design, data were collected from four senior high school teachers in Palembang through a structured 20-item Likert-scale questionnaire. The results indicate varying levels of teacher understanding, despite general procedural compliance through try-outs and dress rehearsals. Students’ readiness was perceived as moderate, with psychological pressure and difficulties in higher-order thinking tasks identified as key challenges. Overall, students demonstrated positive attitudes toward the TKA, though some showed low motivation. The study highlights that successful TKA implementation requires strengthened teacher assessment literacy, student psychological support, and instructional alignment with assessment demands. Keywords: Academic Ability Test, Educational Assessment, Students' Readiness, Teachers’ Perspectives